ANALISIS PENINGKATAN PERUSAHAAN DAN PROPORSI KEUANGAN DARI HARGA SAHAM - Arif Rakhman; Angga Sanita Putra; Gusganda Suria Manda (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2020)
The purpose of this study is to analyze the effect of company growth and the effect of capital structure on the stock prices of Property and Real Estate. This study uses a quantitative approach, which is research that emphasizes its analysis of numerical data (numbers) that are processed by statistical methods. The research method used is descriptive verification method. The data source used is secondary data from the official website www.idx.co.id. The secondary data are the annual financial statements and ICMD of the Property and Real Estate sub-sector companies for the period of 2013 - 2018. Partially, the results of this study indicate that there is no significant effect of the Company's Growth on Stock Prices. In addition, the results of this study also indicate that there is an influence of the Capital Structure on Share Prices. While simultaneously, the results of this study indicate that there is a joint effect of Company Growth and Capital Structure on Share Prices.